O importante valor do deslocamento anterior da aorta abdominal por massa, observado em TC ou RM, no diagnóstico de neuroblastoma em crianças com até 7 anos - Schiavon, Jose Luiz de Oliveira [UNIFESP] (2015)
Objective: Evaluate role of the anterior displacement of the abdominal aorta by tumor, anywhere in the abdomen, or at the level of the contralateral adrenal, in axial CT and/or MRI, to diagnose neuroblastoma, compared to the gold standard pathology report. Methods: This is a retrospective study of patients up to 7 years old who had had abdominal tumors observed on CT and/or MRI, and had their pretreatment images stored in the PACS of the Instituto de Oncologia Pediátrica da Universidade Federal de São Paulo / Grupo de Apoio ao Adolescente e Criança com Câncer IOP-UNIFESP/GRAACC until the end of 2013. The patients? images were classified in consensus by two radiologists for the presence or absence of the anterior displacement of the abdominal aorta. The findings were compared with the pathology report findings (gold standard), and then subjected to the statistical analysis. Results: The anterior displacement of the abdominal aorta, at any level of the abdomen, was present in 26 of the 66 patients included in the study, representing 39.39% of the patients studied. Of these 26 patients, 22 (84.62%) had confirmed neuroblastoma. The other 4 (15.38%) accounted for 3 cases of nephroblastomas and 1 Burkitt's lymphoma, determining a positive predictive value of 84.62% and a specificity of 88.24% for the finding, with a moderate agreement with the pathology report. All these findings were statistically significant with p <0.001. Considering only the displacement of the aorta at the level of the contralateral adrenal, all the 14 patients that displaced the aorta were neuroblastomas, and any non-neuroblastoma tumor had displaced the aorta at that level. Conclusions: We conclude that, when the anterior displacement of the abdominal aorta caused by mass was present at the level of the contralateral adrenal mass, it can be stated that the diagnosis is neuroblastoma, while in cases that the displacement occurs in other abdominal levels, its ability to predict the diagnosis of neuroblastoma is about 85%, all the findings had statistical significance and with a moderate agreement with the pathology report. It should be noted that not all neuroblastoma shifts the aorta, and the neuroblastoma, as in its clinical presentations, may present itself in different ways to imaging. There was no significant influence of tumor size or patients? age in neuroblastoma displacement.